Mechanisms and Characterization of Trichoderma longibrachiatum T6 in Suppressing Nematodes (Heterodera avenae) in Wheat - Zhang, Shuwu; Gan, Yantai; Ji, Weihong; Xu, Bingliang; Hou, Baohong; Liu, Jia (Frontiers in Plant Science, 2017)
Heterodera avenae is an important soil-borne pathogen that affects field crops worldwide. Chemical nematicides can be used to control the nematode, but they bring toxicity to the environment and human. Trichoderma longibrachiatum has been shown to have the ability to control H. avenae cysts, but detailed microscopic observations and bioassays are lacking. In this study, we used microscopic observations and bioassays to study the effect of T. longibrachiatum T6 (TL6) on the eggs and second stage juveniles (J2s) of H. avenae, and investigate the role of TL6 in inducing the resistance to H. avenae in wheat seedling at physiological and biochemical levels. Microscopic observations recorded that TL6 parasitized on the H. avenae eggs, germinated, and produced a large number of hyphae on the eggs surface at the initial stage, thereafter, the eggs were completely surrounded by dense mycelia and the contents of eggs were lysed at the late stage. Meanwhile, the conidia suspension of TL6 parasitized on the surface of J2s, produced a large number of hyphae that penetrated the cuticle and caused deformation of the nematodes. TL6 at the concentration of 1.5×107 conidia ml-1 had the highest rates of parasitism on eggs and J2s, reflected by the highest hatching-inhibition of eggs and the mortality of J2s. In the greenhouse experiments, wheat seedlings treated with TL6 at 1.5×107 conidia ml-1 had reduced H. avenae infection, and increased plant growth significantly compared to the control. The cysts and juveniles in soil were reduced by 89.8% and 92.7%, the juveniles and females in roots were reduced by 88.3% and 91.3%, whereas the activity of chitinase and β-1, 3-glucanase, total flavonoids and lignin contents in wheat roots were increased significantly at different stage after inoculation with the eggs and TL6 conidia in comparison to the control. Maximum activity of chitinase and β-1, 3-glucanase were recorded at the 20th and 15th Days after inoculation with TL6 and thereafter it declined. The maximum contents of total flavonoids and lignin were recorded at the 35th and 40th Days after inoculation with TL6. After being stained with the rapid vital dyes of acridine orange (AO)......